The pan-cancer lncRNA PLANE regulates an alternative splicing program to promote cancer pathogenesis - Liu Teng (Nature Portfolio, 2021)
Genomic amplification of chromosome 3q often encodes proteins that contribute to cancer development. Here the authors identify a non-coding product of the 3q region, the lncRNA PLANE that promotes tumorigenesis through the deregulation of transcriptional corepressor NCOR2 pre-mRNA splicing.